PENCITRAAN STRUKTUR BAWAH PERMUKAAN KOMPLEKS MENGGUNAKAN METODE PRE-STACK DEPTH MIGRATION DENGAN ALGORITMA HORIZON BASED TOMOGRAPHY PADA LAPANGAN “MF-3D” - Muhammad Fahmi; Hernowo Danusaputro; Udi Harmoko (Youngster Physics Journal, 2012)
A research in “MF-3D” field under Pre Stack Depth Migration method for 3D seismic reflection data has been carried out. PSDM selected to describing to perfect subsurface structure that obtain. This research aimed to applying initial interval velocity model determination method in PSDM to obtain better imaging subsurface structure with lateral velocity variation. Initial interval velocity model determination method which used was Dix Transformation and Constrained Velocity Inversion (CVI). Velocity model is quite sufficient to determining interval velocity in shallow layer and inclined flat under Dix Transformation. However, Dix Transformation precisely obtains less sufficient and unstable interval velocity in deeper subsurface layer. CVI conducted to determining initial interval velocity model which required to obtaining better and stable interval velocity in deeper subsurface layer. Both models required to obtaining initial model of 3D seismic section in depth domain as PSDM result. That model will get correction by using Horizon Based Tomography Algorithm in further step. This research yields initial 3D interval velocity model as input for PSDM process. Key Word: Pre Stack Depth Migration (PSDM), Constrained Velocity Inversion (CVI), Horizon Based Tomography